Korelasi Menstruasi dan Dismenore dengan Partisipasi siswi dalam Pembelajaran Penjas - Siti Anisa, - (2020)
Sports education Physical health is one form of effort to create an atmosphere of learning and learning process so that students actively develop their potential. In the process, teaching and learning activities in schools are greatly influenced by the physical condition of students who can mobilize maximum participation in learning. Today many female students complain of pain during learning due to dysmenorrhea so that participation in learning is disrupted, especially physical education. Therefore this research was conducted aiming to determine the relationship between menstruation and dysmenorrhea with student participation in physical education learning. This research method uses descriptive correlational type using quantitative methods, the technique used in this study uses a purposive sampling technique with a sample of 39 class 9 female students at SMPN 10 Bandung, a data collection tool in the form of a questionnaire using Google forms. Based on the results of data analysis, it is known that the probability value of 0.257> 0.05 shows that there is no significant relationship between menstruation and learning participation. While the relationship between dysmenorrhea and learning participation, it is known that the probability value of 0.018 <0.05 indicates that there is a significant relationship between dysmenorrhea and learning participation. the correlation coefficient of -0.378 can be interpreted to have a significant relationship between dysmenorrhea and physical education participation in female students of SMPN 10 Bandung. a negative sign on the correlation coefficient indicates that the higher or more sick dysmenorrhea, the lower the participation of student learning.